Meditation training for people with amyotrophic lateral sclerosis: a randomized clinical trial. (23rd February 2017) - Pagnini, F.; Marconi, A.; Tagliaferri, A.; Manzoni, G. M.; Gatto, R.; Fabiani, V.; Gragnano, G.; Rossi, G.; Volpato, E.; Banfi, P.; Palmieri, A.; Graziano, F.; et al.
Abstract : Background and purpose: Studies investigating psychological interventions for the promotion of well‐being in people with amyotrophic lateral sclerosis (ALS) are lacking. The purpose of the current study was to examine the use of an ALS‐specific mindfulness‐based intervention for improving quality of life in this population. Methods: A randomized, open‐label and controlled clinical trial was conducted on the efficacy of an ALS‐specific meditation programme in promoting quality of life. Adults who received a diagnosis of ALS within 18 months were randomly assigned either to usual care or to an 8‐week meditation training based on the original mindfulness‐based stress reduction programme and tailored for people with ALS. Quality of life, assessed with the ALS‐Specific Quality of Life Revised scale, represented the primary outcome, whilst secondary outcomes included anxiety and depression, assessed with the Hospital Anxiety and Depression Scale, and specific quality of life domains. Participants were assessed at recruitment and after 2, 6 and 12 months. The efficacy of the treatment was assessed on an intention‐to‐treat basis of a linear mixed model. Results: A hundred participants were recruited between November 2012 and December 2014. Over time, there was a significant difference between the two groups in terms of quality of life ( β = 0.24, P = 0.015, d = 0.89). Significant differences between groups over time were also found for anxiety, depression, negative emotions, and interaction with people and the environment. Conclusions: An ALS‐specific meditation programme is beneficial for the quality of life and psychological well‐being of people with ALS.